Metadata network visualizer - Abdul Hamid, Jamaliah; Ibrahim, Hamidah; Selamat, Mohd Hasan; Abdullah, Rusli; Abdullah, Muhamad Taufiq; Nasharuddin, Nurul Amelina; Wan Isa, Wan Malini (2009)
The present invention has been developed to automatically extract document metadata and visualize network display between types of metadata as well as allowing for metadata navigation. The present invention is developed by firstly, developing and using an algorithm to automatically extract publication metadata, secondly, developing and utilizing a more interactive and networked visualizer to display the publication metadata, with more extensive navigational functionalities and finally by providing the option to save the metadata to a database so that search function can be executed. The new metadata extraction algorithm is essentially hand-crafted rules. These rules perform extraction based on combination of parts of speech, publication metadata types, line position, relative position and symbols.